2020
DOI: 10.12984/egeefd.659348
|View full text |Cite
|
Sign up to set email alerts
|

Özel Yetenekli Öğrencilerin Mühendislik Algılarının Çiz-Yaz-Anlat Tekniği Kullanılarak İncelenmesi

Abstract: Bu araştırmada, özel yetenekli öğrencilerin mühendislik algılarının incelenmesi amaçlanmıştır. Araştırmada nitel araştırma yöntemi desenlerinden olgubilim kullanılmıştır. Araştırmanın çalışma grubunu, 2019-2020 Eğitim-Öğretim Yılı birinci döneminde Doğu Anadolu Bölgesi'nde yer alan bir bilim ve sanat merkezinde öğrenim gören 76 özel yetenekli öğrenci oluşturmaktadır. Veriler, çiz-yazanlat tekniği kullanılarak toplanmıştır. Verilerin analizinde içerik analizi yürütülmüştür. Öğrencilerin mühendislik kavramına yö… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 30 publications
0
6
0
3
Order By: Relevance
“…Sontay, Gökdere, and Usta (2014) found in their study that gifted students have higher environmental behavior levels compared to their peers. On the other hand, Nacaroğlu and Bozdağ (2020) found in their study that the perceptions of gifted students towards environmental problems are not sufficient. As a result, in this study, it can be said that the awareness of gifted secondary school students is at a high level.…”
Section: Discussionmentioning
confidence: 83%
“…Sontay, Gökdere, and Usta (2014) found in their study that gifted students have higher environmental behavior levels compared to their peers. On the other hand, Nacaroğlu and Bozdağ (2020) found in their study that the perceptions of gifted students towards environmental problems are not sufficient. As a result, in this study, it can be said that the awareness of gifted secondary school students is at a high level.…”
Section: Discussionmentioning
confidence: 83%
“…However, there are few children who think that engineers are woman. When the literature is examined, no such result has been found for preschool children, and it is seen that in studies conducted at primary and secondary school level, students mostly perceive engineers as male (Chou & Chen, 2017;Çil & Özlen, 2019;Hyeonyeong vd., 2012;Koyunlu Ünlü & Dökme, 2017;Nacaroğlu & Arslan, 2020). Furthermore, Gülhan and Şahin (2018) noted that as the grade level increases, girls' perceptions of female engineers decrease.…”
Section: Discussionmentioning
confidence: 99%
“…Ergün (2018) and Çakmak et al, (2019) also ascertained that secondary school pupils think of engineers as male, working in road construction, construction workers, drudgers or repairmen. Similarly, Nacaroğlu and Arslan (2020) examined the engineering perceptions of gifted students aged between 6 and 20 and concluded that they mostly reflected common social perceptions such as being a civil engineering, computer engineering and being a male occupation. A study conducted with 5th grade pupils, it has been determined that the pupils similarly have stereotypical perceptions such as civil engineer and male, intelligent and rich (Çil & Özlen, 2019).…”
Section: Engineering and Stemmentioning
confidence: 99%
“…In order to determine students' opinions about scientists, a test called "draw a scientist" (DAST) is encountered. Developed by Chambers (1983), DAST has been applied until today and has been easily used in applications for illiterate preschoolers to adult individuals (Basay & Aytar, 2019; Duran & Bayar, 2019;Nacaroglu & Arslan, 2020;Ruiz-Mallén, & Escalas, 2012;Yazici, et al, 2021). Seven indicators of standard scientist drawings are presented in student drawings (Chamber, 1983): (1) lab coat, (2) glasses, (3) facial hair, (4) research symbols, (5) knowledge symbols, (6) technological product, and (7) various writings.…”
Section: Introductionmentioning
confidence: 99%